Penyisihan Parameter Organik dan Analisis Kualitas Lumpur Limbah Cair Rumah Potong Ayam dengan Moving Bed Biofilm Reactor - Qatrunada, Sekar Huwaidah; Novembrianto, Rizka; Ali, Munawar (Jurnal Serambi Engineering, 2025)
The disposal of wastewater containing high levels of organic parameters can trigger bacterial growth, which can lead to a decrease in dissolved oxygen in the water. This research uses MBBR technology to degrade organic parameters. The aim of this research is to compare the optimum media types for the degradation of organic pollutants and to analyse the MLSS and SVI values to determine the quality of the sludge produced. The variation used in this study is the type of media used is sponge media and K5 hardness with the treatment of both types of media using residence time for 2 hours, 4 hours, 6 hours, 8 hours and 10 hours. In the study, the seeding and acclimation process was carried out first until it met the specified design criteria. The results indicated that the best media for COD and total nitrogen removal were the sponge media with a removal percentage of 56% and 48% at a retention time of 10 hours. In the analysis of MLSS and SVI, the highest MLSS value was obtained in Kaldness K5 and there was an increase in SVI at each retention time for both. From this study it can be concluded that Kaldness K5 is more dominant in a suspended growth system than a sponge, but the greatest removal of organic pollutants is in sponge media which is more dominant in attached growth.